Single cell analysis of neutrophils NETs by microscopic LSPR imaging system - Mohamed Ali, Riyaz Ahmad; Mita, Daiki; Espulgar, Wilfred; Saito, Masato; Nishide, Masayuki; Takamatsu, Hyota; Yoshikawa, Hiroyuki; Tamiya, Eiichi (MDPI, 2020)
A simple microengraving cell monitoring method for neutrophil extracellular traps (NETs) released from single neutrophils has been realized using a polydimethylsiloxane (PDMS) microwell array (MWA) sheet on a plasmon chip platform. An imbalance between NETs formation and the succeeding degradation (NETosis) are considered associated with autoimmune disease and its pathogenesis. Thus, an alternative platform that can conduct monitoring of this activity on single cell level at minimum cost but with great sensitivity is greatly desired. The developed MWA plasmon chips allow single cell isolation of neutrophils from 150 μL suspension (6.0 × 105 cells/mL) with an efficiency of 36.3%; 105 microwells with single cell condition. To demonstrate the utility of the chip, trapped cells were incubated between 2 to 4 h after introducing with 100 nM phorbol 12- myristate 13-acetate (PMA) before measurement. Under observation using a hyperspectral imaging system that allows high-throughput screening, the neutrophils stimulated by PMA solution show a significant release of fibrils and NETs after 4 h, with observed maximum areas between 314–758 μm2. An average absorption peak wavelength shows a redshift of Δλ = 1.5 nm as neutrophils release NETs.